2014
DOI: 10.1155/2014/126961
|View full text |Cite
|
Sign up to set email alerts
|

Postactivation Potentiation Biases Maximal Isometric Strength Assessment

Abstract: Postactivation potentiation (PAP) is known to enhance force production. Maximal isometric strength assessment protocols usually consist of two or more maximal voluntary isometric contractions (MVCs). The objective of this study was to determine if PAP would influence isometric strength assessment. Healthy male volunteers (n = 23) performed two five-second MVCs separated by a 180-seconds interval. Changes in isometric peak torque (IPT), time to achieve it (tPTI), contractile impulse (CI), root mean square of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
1
7
0
1
Order By: Relevance
“…The results of this study indicate that isometric, concentric, and eccentric contractions with short-term recovery periods improved maximal torque performance. The results of this study are in line with the results by Buadry and Duchateau (2007) and Lima et al (2014) regarding the effect of isometric and concentric contractions (14,19). However, no research was found to contradict our findings.…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study indicate that isometric, concentric, and eccentric contractions with short-term recovery periods improved maximal torque performance. The results of this study are in line with the results by Buadry and Duchateau (2007) and Lima et al (2014) regarding the effect of isometric and concentric contractions (14,19). However, no research was found to contradict our findings.…”
Section: Discussionsupporting
confidence: 92%
“…They observed that PAP increased jump height (5.03%), maximal force (4.94%), acceleration impulse (9.49%) in the drop jump, and improved knee extension maximal torque by 6.12%. Recently, Johnson et al (12) demonstrated that PAP using drop jumps increased peak twitch torque, rate of strength development, and impulse significantly in athletes during 9 sets of 3 c electrically evoked maximal twitches interspersed, suggesting that PAP can enhance the forcegenerating capacity of the muscle (2,13,16). However, whether PAP could influence back squat performance using multiple sets is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that muscular power output can be increased by inducing a post-activation potentiation (PAP) effect with heavy resistance exercises (e.g., 5-RM back squat) [ 1 , 2 , 3 , 4 , 5 , 6 ]. PAP is defined as an increase in muscle performance after a conditioning contraction [ 7 ].…”
Section: Introductionmentioning
confidence: 99%